Adat Pernikahan Mandailing sebagai Sumber Pembelajaran Nilai-nilai Karakter dalam Pendidikan - Imelda Sari; Mustika Sari; Rafikah Hanum Rambe; Riski Towilah Nasution; Rahmi Wahyuni (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
The Mandailing wedding tradition is one of Indonesia’s rich cultural heritages that embodies noble values and can serve as a valuable source for character education. Through ceremonies that emphasize mutual cooperation (gotong royong), deliberation (musyawarah), respect for parents, and religiosity, the Mandailing community has preserved and transmitted moral and character education across generations. This study aims to examine the character values embedded in the Mandailing wedding tradition and identify their relevance to educational practices. The research employs a descriptive qualitative approach through literature review and cultural observation. The findings indicate that the Mandailing wedding tradition contains essential values such as responsibility, cooperation, honesty, and respect, which can be integrated into the learning process to cultivate students with noble character and a deep appreciation for their cultural heritage.